Sobre Paulo Freire: Os contornos discursivos de uma vida - Pollyanna Júnia Fernandes Maia Reis (2018)
This study aims to investigate the discursive construction of Paulo Freire 's images, unveiled from Paulo Freire' s work: uma biobibliografia (1996), organized by Moacir Gadotti. It is a book that we take as a life narrative (MACHADO, 2009), since it deals with what can be considered as a social object, leaving behind the model of Bertaux (2003, 34) a part of the life of this subject: in particular, in our view, for seeking to represent the course of an existence; in particular, of a remarkable man in the national and global scenarios. We are interested, based on the First part of the study, to ascertain from which voices the figure of Paulo Freire is contoured, seeking to identify and analyze the images instituted through the linguistic-discursive constructions of those who author the texts: Ana Maria Araújo Freire, widow of the educator; Moacir Gadotti, director of the Paulo Freire Institute (IPF), homage to the theoretician; Carlos Alberto Torres, Latin American biographer of Paulo Freire; and; Heinz-Peter Gerhardt, author of Arqueologia de um pensamento, a work based on the theoretical assumptions of Freire. In order to anchor our analysis, we used the contributions of the Sémiolinguistique Theory of Charaudeau (2006a, 2008, 2010), based on the notions of communication contract and readings, as well as the modes of discourse organization; to the considerations of Bertaux (1976, 2003) about the term récit de vie; to the theorizations of Machado (2009, 2012, 2013, 2014a, 2014b, 2015, 2016), regarding the life narratives; and to Gardner's (1999) work on extraordinariness. In view of the foregoing, we shall examine the communication contract established in the aforementioned work, paying attention to the way in which the construction of Paulo Freire's image was elaborated as the object of a life narrative as a hero-alike or humanized-being, the subjects involved and the socio discursive identities manifest in the enunciative scene and how the modes of organization of discourse proposed by Charaudeau (2008) were useful for us to be able to interpret, in a discursive way, the construction, through words, of a man, its history and its work within the scope of a life narrative.